An agnotological analysis of APIs: or, disconnectivity and the ideological limits of our knowledge of social media. Issue 1 (1st January 2019) - John, Nicholas A.; Nissenbaum, Asaf
Abstract: Adopting an agnotological perspective, this article extends the critical literature on APIs (application programing interfaces) by systematically showing that social media APIs are largely blind to acts of disconnectivity such as unfriending and unliking. We do this through analysis of the traces of social media usage that are not accessible through APIs as gleaned from the technical documentation published for developers by 12 major SNSs. Our findings make two main contributions. First, we show for the first time that APIs offer virtually no access to data about disconnectivity. Second, we show that APIs offer a very limited historical perspective, particularly regarding disconnectivity. However, for types of users that might spend money on advertising, far more historical and disconnectivity-oriented information is accessible through the API. This has practical consequences for research and contributes to an agnotology of social media that sheds critical light on the advertiser-friendly atmosphere of connectivity that social media try to create.